Des Afro-descendants dans un pays « blanc ». Vers l’effectivité de l’égalité raciale au Costa Rica - Sophie Simon (Cahiers des Amériques Latines)
Costa Rica is a democratic State and enjoys an abundant anti discriminatory legislation. However the situation of the afro Costa Ricans is not enviable. However the society is a melting pot, it defines itself as being white and look down on everything and everyone that is not like it. The most discriminated are undoubtedly the afro descendents. In fact, they are not the object of a specific legislation as indigenous people are. The general legislation is not adapted to their needs and when they try to have their rights recognized by the administration or by tribunals, it happens often that the reaction of the civil servant is a real incomprehension. Indeed, at no stage of the education program, primary school, secondary or even superior, is made a real reference to the existence and to the contributions of the Afro Costa Rican to the development of the present Costa Rican Nation. Invisiblized, misunderstood and discriminated, they hardly survive, living the difference that defines them. However Costa Rica would gain to recognize its pluri ethnic statute.